Streaming video strategies : building next-gen apps and sites - Miller, Carolyn Handler; Kane, Frank (O'Reilly Media, Inc., 2022)
Video is an essential tool for businesses and a key driver in consumer sales. But consumers expect the seamless viewing experiences they get on specialized streaming sites like Netflix and YouTube across every company everywhere they watch. Building video that meets those expectations into your sites and apps means dealing with complex challenges. In this report, Carolyn Handler Miller and Frank Kane help you think through decisions about building video at your company--whether you're a founder considering the role of video in your app, a product manager or team lead overseeing video infrastructure, or a developer executing on user experience. You'll explore a solid framework for incorporating video into your websites and apps that considers your existing infrastructure so that you can deliver seamless, high-quality video experiences that drive real results. Four case studies then show how real companies have successfully built video experiences into their businesses' software architecture. This report helps you: Understand the changing role of video for businesses today Appreciate the unique challenges of building video Decide whether to design and build video infrastructure yourself or partner with a third-party expert.